2006
DOI: 10.1021/bi060612h
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Force Microscopy Reveals DNA Bending during Group II Intron Ribonucleoprotein Particle Integration into Double-Stranded DNA

Abstract: The mobile Lactococcus lactis Ll.LtrB group II intron integrates into DNA target sites by a mechanism in which the intron RNA reverse splices into one DNA strand, while the intron-encoded protein uses a C-terminal DNA endonuclease domain to cleave the opposite strand and then uses the cleaved 3' end to prime reverse transcription of the inserted intron RNA. These reactions are mediated by an RNP particle that contains the intron-encoded protein and the excised intron lariat RNA, with both the protein and base … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
(93 reference statements)
0
15
0
Order By: Relevance
“…Additionally, decreased efficiency could result from suboptimal base-pairing interactions with the intron RNA, deleterious effects of nucleotide substitutions on intron RNA activity, occlusion of some target sites by proteins, or contributions of other factors, such as duplex stability or higher-order DNA structure (30). Recent studies showed that integration of Ll.LtrB intron RNPs results in bending of the target DNA, and computational analysis suggested that DNA bendability in addition to sequence may influence DNA integration efficiency (29). We anticipate that the algorithm will continue to improve as larger databases become available and more information about other factors is incorporated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, decreased efficiency could result from suboptimal base-pairing interactions with the intron RNA, deleterious effects of nucleotide substitutions on intron RNA activity, occlusion of some target sites by proteins, or contributions of other factors, such as duplex stability or higher-order DNA structure (30). Recent studies showed that integration of Ll.LtrB intron RNPs results in bending of the target DNA, and computational analysis suggested that DNA bendability in addition to sequence may influence DNA integration efficiency (29). We anticipate that the algorithm will continue to improve as larger databases become available and more information about other factors is incorporated.…”
Section: Discussionmentioning
confidence: 99%
“…Bottom-strand cleavage occurs at position +9 from the insertion site and requires additional interactions between the IEP and the 3 ′ exon, the most critical being recognition of T+5 (Singh and Lambowitz 2001). Binding of the RNP to the 5 ′ and 3 ′ DNA exons bends the target DNA, with the bend angle increasing when the cleaved 3 ′ end is repositioned from the En to RT active site for initiation of reverse transcription (Noah et al 2006). Because reverse splicing into the DNA target site is reversible and the equilibrium favors intron excision, the reaction must be driven forward by the initiation of cDNA synthesis, which blocks the 3 ′ -splice site and prevents excision (Aizawa et al 2003).…”
Section: Dna Target Site Recognition By Group II Intron Rnpsmentioning
confidence: 99%
“…DIVa nevertheless remains a high-affinity binding site for the IEP, reflecting a critical role of this interaction in nucleating RNP assembly and positioning the IEP for initiation of TPRT (65). After splicing, the IEP remains tightly bound to the intron lariat in a stable RNP that promotes retrohoming (30,42).…”
Section: Iep Expressionmentioning
confidence: 99%
“…Bottom-strand cleavage between positions +9 and +10 of the DNA target site occurs after a lag and requires additional interactions of the IEP with the 3′ exon, most critically recognition of T+5. Atomic force microscopy showed that the binding of RNPs bends the target DNA into two progressively sharper bend angles, the first correlated with 3′-exon interactions that position the scissile phosphate at the En active site for bottom-strand cleavage, and the second with repositioning of the 3′ end of the cleaved strand from the En to the RT active site for initiation of cDNA synthesis (42). Notably, even with this DNA bending, the distance between DNA target site residues T-23 and T+5 recognized by the IEP is longer than can be spanned readily by a single IEP molecule.…”
Section: Dna Target Site Recognitionmentioning
confidence: 99%
See 1 more Smart Citation